Fetal Beckwith-Wiedemann syndrome associated with abnormal quad test, placental mesenchymal dysplasia and HELLP syndrome. Issue 6 (24th June 2021) - Jatavan, Phudit; Tongsong, Theera; Traisrisilp, Kuntharee
Abstract : We describe a unique case of Beckwith-Wiedemann syndrome (BWS). A 29-year-old woman with ultrasound and clinical findings, specific to BWS is described. Important insights gained from this study are as follows: (1) quad test may be very useful to increase awareness of BWS. This is the first report, which demonstrated that elevated inhibin-A is related to BWS. Unexplained elevation of serum biomarkers, especially all the four markers, should raise awareness of BWS. (2) Early provisional diagnosis in this case was based on the findings of omphalocele, placental mesenchymal dysplasia and abnormal quad test. (3) Follow-up scans are important for late-occurring supportive findings, such as macroglossia, ear abnormalities and visceromegaly. (4) BWS is strongly associated with preeclampsia, which tended to be more severe and of earlier-onset. (5) Molecular genetic analysis is helpful, but not always necessary in cases of fulfilment of clinical criteria like in this case.